Producción e incremento volumetrico de cordia alliodora (laurel) dentro de sistemas agroforestales en cinco propiedades de la Parroquia Puerto Limón, Cantón Santo Domingo año 2015 - Jumbo Burbano, Danny Fabian (2016)
The work was carried out in five agroforestry farms of the parish Puerto Limón, province of Santo Domingo de los Tsáchilas. The first phase consisted in carrying out forest censuses of 200 Cordia alliodora trees in each of the farms where the diameter (DAP) of the trees with d ≥20 cm was measured and the commercial height of the trees with Hc ≥14 M, to determine the basal area and calculate the volumetric increase of wood in these SAF. The second phase consisted in determining the morphological and phytosanitary characteristics of the trees before being harvested, in which the shape of the stem was evaluated by classifying them into six classes: R: straight; P: little winding; Rb: straight bifurcated; Pb: little sinuous bifurcated; M: very winding and Mb: very winding bifurcated. The phytosanitary status of each tree was also evaluated and classified into four classes: S: healthy; Cr: broken glass; PE: with pest or sick and Ma: killstick in laurel (Phoradendrum spp.). The analysis of variance of the two selected variables was carried out and indicates that there are no significant differences in the growth of the Cordia alliodora trees since the coefficient of variation indicates that there is heterogeneity in the five agroforestry systems under study in the basal area (AB) and standing volume (PV), the probability being less than the value of the F test in both cases. To determine the losses of the post-harvesting wood, a series of formulas were applied which determined the percentages of wastage of the whole stage of the forest harvest; The following variables Volume on Foot (PV), Volume of waste of each log (Vdt), Cutting volume of the chainsaw (Vcm) and Volume of the jampa (Vj) were considered. The owners of the farms apply practices that favor regeneration, control pests, know shifting shifts and shade distribution in SAF. It is recommended to study the insertion of SAF throughout the province of Santo Domingo.